2010
DOI: 10.1111/j.1540-8175.2009.01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Right Ventricular Diastolic Function by Tissue Doppler Imaging in Patients with Acute Right Ventricular Myocardial Infarction

Abstract: Right ventricular TDI diastolic parameters are abnormal in patients with RVMI. The method of recording the velocities and time intervals are simple and can be used to assess right ventricular diastolic function in patients with RVMI. (Echocardiography 2010;27:539-543).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…Our study also was concordant with Gopalan et al, who studied the echo assessment of RV function in inferior wall MI and angiographic correlation to proximal RCA stenosis, and concluded that TAPSE was significantly lower in patients with proximal RCA lesion and both two groups of patients according to presence or absence of proximal RCA stenosis had no significant differences in baseline variables like age, sex, prevalence of hypertension and diabetes (23). On the other hand the present study disagreed with Rudski et al, who demonstrated the guidelines for the Echo Assessment of the Right Heart in Adults, they concluded that cut off value of TAPSE was less than 17 mm indicate RV dysfunction, but our study demonstrate ≤ 20 mm cut off value of TAPSE was predicted proximal RCA lesion (24), and disagreed with El Sebaie et al, who assessed the right ventricular echocardiographic parameters for prediction of proximal right coronary artery lesion in patients with inferior wall myocardial infarction who found that there is no significant difference according to right ventricular function which assessed by TAPSE in patients with or without proximal RCA lesion that may be due to echo assessment of RV function in both two previous study was done before reperfusion therapy but in our study some of our patients undergone to reperfusion therapy as there is a possibility of recovery of RV function that before echo assessment (25).According to TDI assessment of RV function for patients with or without proximal RCA lesion the present study agreed with Ozdemir et al, who studied the new parameters in identification of RV MI and proximal RCA lesion , they concluded that peak velocity of RV free wall (Sm) is ≤ 10.41cm/s predicted proximal RCA lesion with 64.7%, 75%, 77.8% and 61.1% sensitivity and specificity, negative predictive value and positive predictive value respectively (26).Current study was also concordant with Mukhaini et al, who studied the Assessment of RV diastolic function by TDI in patients with acute RV MI, and proved that RV diastolic function was significantly lower in patients with proximal RCA lesion compared to patients without proximal RCA lesion (27). Again the present study also was agreed with Kakouros et al, who studied the Tissue Doppler imaging of the tricuspid annulus and myocardial performance index in the evaluation of right ventricular involvement in the acute and late phase of a first inferior myocardial infarction, how found that the peak systolic velocity (S') of the tricuspid annulus was significantly lower in patients with proximal RCA lesion (28).…”
Section: Discussionsupporting
confidence: 81%
“…Our study also was concordant with Gopalan et al, who studied the echo assessment of RV function in inferior wall MI and angiographic correlation to proximal RCA stenosis, and concluded that TAPSE was significantly lower in patients with proximal RCA lesion and both two groups of patients according to presence or absence of proximal RCA stenosis had no significant differences in baseline variables like age, sex, prevalence of hypertension and diabetes (23). On the other hand the present study disagreed with Rudski et al, who demonstrated the guidelines for the Echo Assessment of the Right Heart in Adults, they concluded that cut off value of TAPSE was less than 17 mm indicate RV dysfunction, but our study demonstrate ≤ 20 mm cut off value of TAPSE was predicted proximal RCA lesion (24), and disagreed with El Sebaie et al, who assessed the right ventricular echocardiographic parameters for prediction of proximal right coronary artery lesion in patients with inferior wall myocardial infarction who found that there is no significant difference according to right ventricular function which assessed by TAPSE in patients with or without proximal RCA lesion that may be due to echo assessment of RV function in both two previous study was done before reperfusion therapy but in our study some of our patients undergone to reperfusion therapy as there is a possibility of recovery of RV function that before echo assessment (25).According to TDI assessment of RV function for patients with or without proximal RCA lesion the present study agreed with Ozdemir et al, who studied the new parameters in identification of RV MI and proximal RCA lesion , they concluded that peak velocity of RV free wall (Sm) is ≤ 10.41cm/s predicted proximal RCA lesion with 64.7%, 75%, 77.8% and 61.1% sensitivity and specificity, negative predictive value and positive predictive value respectively (26).Current study was also concordant with Mukhaini et al, who studied the Assessment of RV diastolic function by TDI in patients with acute RV MI, and proved that RV diastolic function was significantly lower in patients with proximal RCA lesion compared to patients without proximal RCA lesion (27). Again the present study also was agreed with Kakouros et al, who studied the Tissue Doppler imaging of the tricuspid annulus and myocardial performance index in the evaluation of right ventricular involvement in the acute and late phase of a first inferior myocardial infarction, how found that the peak systolic velocity (S') of the tricuspid annulus was significantly lower in patients with proximal RCA lesion (28).…”
Section: Discussionsupporting
confidence: 81%
“…18,19 Tissue Doppler imaging of the lateral mitral and tricuspid annuli was performed as previously described with instrument setting adjusted to record the high-amplitude/low-velocity myocardial signals. [20][21][22] Multiple measurements (3)(4)(5) were averaged for each Doppler tissue parameter and early diastolic as well as late diastolic tissue velocities over the mitral and tricuspid annuli were measured.…”
Section: Echocardiographic Examinationmentioning
confidence: 99%
“…PW-TDI velocity at tricuspid lateral annulus lowered in RVMI patients, and is a convenient and feasible method to evaluate RV function [20,21]. Et′, At′, St′ in Group I were significantly lower than in Group II respectively (P b 0.01).…”
mentioning
confidence: 80%